The impact of dance on human health - Marosz, Szymon; Borkowska, Aleksandra; Borkowska, Katarzyna; Krysiak, Patrycja; Kuligowska, Monika; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2022)
Introduction: Dancing is one of the many forms of physical activity. Dance performs a wide variety of functions, because on the one hand it satisfies the spiritual and aesthetic experience, and on the other hand, it can be a cultural entertainment or a form of physical fitness training. Moreover, dance has pedagogical values, shapes a person's personality, motor skills, develops the mind, and is a very good educational tool for children. Dance is a form of exercise and this prevents civilization diseases such as obesity, overweight, atherosclerosis, hypertension, and diabetes. Therefore, in order to maintain the well-being and health of the body, it is very important to take up physical activity in your free time. The aim of the study: The aim of the study is to find out how dancing affects students' health and to compare the results of the research with the available knowledge. Material and method: The paper uses standard criteria as the research method. Additionally, during the literature review on PubMed and Google Scholar platforms, keywords such as dance, choreotherapy, training. Summary: The results of our research are comparable with the results of other studies. They indicate the positive influence of dance on human health. It affects not only the physical sphere, but also the mental one. Dance is increasingly used in the treatment of various diseases. Dancers see the difference in improving their body flexibility, coordination and strength.In additional, dancing affects the feeling of greater body awareness during movement.